A comparative study on sedative and cardiorespiratory effects of clonidine and dexmedetomidine added to ropivacaine in supraclavicular brachial plexus block in upper extremity surgery - Anamitra Mandal,; Sourav Naiya ,; Sarbari Swaika,; Swarup Datta,; Swapnadeep Sengupta, (Asian Journal of Medical Sciences, 2023)
Background: Supraclavicular brachial plexus block is widely used peripheral nerve block technique used for surgery of the upper extremity. Several drugs have been used with local anesthetic as adjuvants for rapid, dense, and prolonged analgesia. Aims and Objectives: The aims and objectives of the study are to compare the degree of sedation and cardiorespiratory effects of clonidine and dexmedetomidine added to ropivacaine in supraclavicular brachial plexus block. Materials and Methods: A double-blinded comparative study was done on eighty patients who were randomly allocated equally into two groups and received clonidine and dexmedetomidine added to ropivacaine 0.5%. Intraoperative degree of sedation and cardiorespiratory parameters were monitored in regular intervals and compared to find difference. Results: Heart rate was consistently lower with dexmedetomidine. Systolic, diastolic, and mean arterial pressures (MAPs) were comparable in both groups at all time points except at 45 min when diastolic and MAP were lower with dexmedetomidine and it was statistically significant. Sedation score in Group D was higher except at 5 min and difference was statistically significant. All patients in both groups were sedated and easily arousable. There was statistically significant difference in peroperative oxygen saturation between the groups although it was clinically not significant. Conclusion: There was more hemodynamic effect of dexmedetomidine than clonidine but these effects can be managed by medication easily. In addition to this, it was found that dexmedetomidine provides conscious sedation without any respiratory depression. Comparing the risk and benefit dexmedetomidine can be used with local anesthetic in supraclavicular brachial plexus block in upper extremity surgery.